PEDAGOGICAL INNOVATIONS IN PHYSICAL EDUCATION: CURRICULAR INTEGRATION AND IMPACTS ON THE INTEGRAL DEVELOPMENT OF STUDENTS IN THE MODULAR ORGANIZATION TEACHING SYSTEM – SOME IN A QUILOMBOLA SCHOOL IN AMAPÁ - Alves, Olinda Rocha; Santos, Maelio Cesar Freitas dos; Gomes, Sarah Medeiros Souto; Silva, Vânia Aparecida Santos da; Soares, Evódia Simone Monteiro; Simas, Simone Silva; Lins, Daniela Alves dos Santos; Santos, Cilene; Dias, João Carlos Benício; Carmo, Ana Maria Picanço do; Sousa, Edson Canuto de; Ferreira, Anselmo Accioly Francisco; et al. (Seven Editora, 2025)
This study analyzed pedagogical innovations in school Physical Education, curriculum integration, and their impacts on the holistic development of students in the Modular Education System (SOME) at a quilombola school in Amapá, Brazil. Through an integrative literature review (2010–2025), innovative pedagogical practices were identified that value local culture, promote interdisciplinarity, and strengthen students’ identity. It was observed that modular education requires differentiated strategies, active methodologies, and context-specific teacher training. Despite structural challenges, Physical Education emerges as a space for cultural resistance, meaningful learning, and citizenship development. The study highlights the need for public policies supporting continuous teacher education, pedagogical autonomy, and recognition of quilombola knowledge. Gaps were identified in quantitative and longitudinal studies, indicating directions for future research.DOI: https://doi.org/10.56238/sevened2025.038-020